Physical and chemical reaction sensing in a mixed aqueous solution via metal‐organic framework thin‐film coated optical fiber. Issue 1 (30th September 2019) - Nazari, Marziyeh; Amini, Abbas; Hill, Matthew R.; Cheng, Chun; Samali, Bijan
Abstract: A metal‐organic framework thin‐film (UiO‐66) optical fiber platform is built up as a data processing sensory system to detect water contaminations. A simple scale‐up approach is utilized to design a water‐stable UiO‐66 sensor at the tip (end face) of a conventional single mode optical fiber (SMF‐28) for detecting rhodamine‐B and methyl viologen in a mixed aqueous solution. The optical detection method was based on Fabry–Perot Interferometry, and the interference signal was analyzed by the fast Fourier transform (FFT) technique. Combining two contaminants in water produces a complex physical and chemical phenomena, and the FFT clearly showed it as a particular frequency related to a specific analyte type.